A method for preparing mixed-valence copper ion antibacterial masterbatch

By preparing mixed valence copper ion antibacterial masterbatches, the core-shell structure of 0-valence, 1-valence and 2-valence copper ions and three-dimensional aerogel network structure are solved, and the problem of insufficient antibacterial performance of existing silver ions and divalence copper is solved. , achieving stronger antibacterial effects and environmentally friendly use.

CN115160605BActive Publication Date: 2024-12-31沪本新材料科技(上海)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210704906.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-21
Publication Date
2024-12-31
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

The existing silver ion antibacterial masterbatches are expensive and may enter the human body, which has health hazards. The existing commercial copper compounds are mainly insoluble divalent copper, which lacks antibacterial performance and is difficult to meet environmental and economic needs.

Method used

The mixed valent copper ion antibacterial masterbatch is prepared through redox reaction, combining 0-valent, 1-valent and 2-valent copper ions to form a core-shell structure and a three-dimensional aerogel network Cu@Cu2O, increasing the surface area and adsorption force, and improving antibacterial performance.

Benefits of technology

A stronger antibacterial effect is achieved. The zero-valent copper quickly damages the cell membrane, the one-valent copper binds to protein to inactivate it, the two-valent copper damages DNA, and the three-dimensional aerogel network adsorbs more bacteria, significantly improving the antibacterial performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115160605B_ABST
    Figure CN115160605B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a mixed-valence copper ion antibacterial masterbatch, and the specific steps of the method are as follows: 1) Preparation of Cu@CuO: stirring an emulsion containing ethanol, deionized water, glycerol and a soluble copper salt until uniform, transferring it to a high-pressure reactor for reaction, cooling, washing and drying to obtain Cu@CuO. 2) Preparation of a three-dimensional aerogel network Cu@Cu 2 Preparation of Cu@CuO: Soluble copper salt and strong base were added to deionized water and stirred until uniform, then transferred to a three-necked flask and continued to stir while passing inert gas; ethanol was added to the mixture, and the reducing agent solution was quickly added to the solution during stirring. After 15-20 min, the mixture was centrifuged and washed to obtain a three-dimensional aerogel network Cu@Cu 2 O. 3) Cu@CuO and three-dimensional aerogel network Cu@Cu prepared in step 1) and step 2) are 2 O is mixed with polyethylene powder to obtain a mixed powder, and then the mixed powder is heated to 130-210° C. by a twin-screw extruder granulator to melt and extrude, and then air-cooled and pelletized to obtain a mixed-valence copper ion antibacterial masterbatch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, in particular to a method for preparing mixed-valence copper ion antibacterial masterbatch. Background Art

[0002] Antibacterial masterbatch can meet people's needs for health and environmental protection. Therefore, it is increasingly valued and has huge market potential.

[0003] In the past decade, silver ion antibacterial masterbatch has been widely used as a representative of antibacterial masterbatch. However, silver ion antibacterial masterbatch also has certain application limitations. On the one hand, the price of silver is expensive, which leads to the high price of silver ion masterbatch. On the other hand, products made of silver ion antibacterial masterbatch are in contact with human skin for a long time, and silver ions will enter the human body and accumulate, endangering human health.

[0004] Therefore, it is of great significance to develop an antibacterial masterbatch with low price and low harm. Studies have shown that copper can not only inhibit the growth of bacteria, viruses and fungi, but also promote the metabolism of human skin, and the copper ions that enter the human body can also be easily excreted from the body by human metabolism. Therefore, using copper instead of silver to make copper ion antibacterial masterbatch has become a consensus and popular trend in the industry today. At present, the commercial copper compounds used in agriculture are mainly insoluble copper (+2 valence) compounds. There are many mechanisms of action related to the biological activity of copper, which are all related to its oxidation state. Studies have reported that the antibacterial activity of monovalent copper is higher than that of divalent copper. It is reported that the release of ionic copper on the surface of metallic copper is also the reason for its antibacterial property. In general, monovalent copper and metallic copper have stronger antibacterial properties than divalent copper. (Quoted from "Cu-Si nanocomposites containing mixed valence Cu: Improving the antimicrobial activity of copper agents" by Shanghai Pesticide Research Institute), therefore, it is necessary to use mixed valence copper ions to improve the antibacterial properties of masterbatch.

[0005] To this end, the present invention provides a method for preparing a mixed-valence copper ion antibacterial masterbatch. Compared with the mixing of two mixed-valence copper ions, the mixed-valence copper ions in the present invention are 0-valence, 1-valence and 2-valence copper ions mixed at the same time, and different core-shell structures are prepared through two redox reactions. The core-shell structure has a larger area and can contact more bacteria, which can improve the antibacterial performance of the material faster and better. And a three-dimensional aerogel network Cu@Cu 2 O, aerogel has strong adsorption capacity and large porosity, which can adsorb more bacteria, inactivate bacteria quickly, and have a better antibacterial effect. Summary of the invention

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a mixed-valence copper ion antibacterial masterbatch, comprising the following steps:

[0007] The present invention provides a method for preparing a mixed-valence copper ion antibacterial masterbatch, characterized in that the method comprises the following specific steps:

[0008] 1) Preparation of Cu@CuO:

[0009] (1) An emulsion containing 20-30 mL of ethanol, 12-20 mL of deionized water, 6-9 mL of glycerol, and 3-5 g of a soluble copper salt was magnetically stirred for 1-2 h until uniformly mixed. The emulsion was then transferred to a high-pressure reactor and reacted at 200-240 °C for 6-8 h, and then naturally cooled to room temperature.

[0010] (2) Take the precipitate out of the reactor, wash it with ethanol 3 to 5 times, and heat it at 60 to 80 °C.

[0011] After drying in air for 2-3 h, Cu@CuO was obtained.

[0012] 2) Three-dimensional aerogel network Cu@Cu 2 Preparation of O:

[0013] (1) Add 4-6 g of soluble copper salt and 1.6-2.4 g of strong base to deionized water and stir for 1-2 h until uniform. Then transfer the mixture to a three-necked flask and continue stirring for 20-30 min. Then, introduce inert gas for 20-30 min.

[0014] (2) Add 100-150 μL of ethanol to the above mixture, dissolve 12-16 g of reducing agent in deionized water, and quickly add the reducing agent solution to the above solution during stirring. After 15-20 min, centrifuge and wash with deionized water and anhydrous ethanol for 3-5 times to obtain a three-dimensional aerogel network Cu@Cu 2 O.

[0015] 3) The Cu@CuO and three-dimensional aerogel network Cu@Cu prepared in step 1) and step 2) are 2 O and polyethylene powder are mixed at a stirring speed of 550-750 rpm for 15-30 min to obtain a mixed powder, and then the mixed powder is heated to 130-210°C by a twin-screw extruder granulator to melt and then extruded, and then air-cooled and pelletized to obtain a mixed-valence copper ion antibacterial masterbatch.

[0016] Preferably, in step 1), the soluble copper salt is one or a combination of copper chloride, copper sulfate or copper acetate.

[0017] Preferably, in the step 2), the strong base is one of sodium hydroxide and potassium hydroxide or a combination thereof.

[0018] Preferably, in the step 2), the inert gas is one or a combination of argon or nitrogen.

[0019] Preferably, in step 2), the reducing agent is one or a combination of hydrazine hydrate, sodium borohydride or hypochlorous acid.

[0020] Preferably, in the step 3), the nine-stage processing temperatures of the twin-screw extruder are set as follows: zone 1 temperature 130°C, zone 2 temperature 165°C, zone 3 temperature 188°C, zone 4 temperature 198°C, zone 5 temperature 210°C, zone 6 temperature 210°C, zone 7 temperature 200°C, zone 8 temperature 180°C, zone 9 temperature 166°C.

[0021] Compared with the prior art, the method for preparing the mixed-valence copper ion antibacterial masterbatch prepared by the method described in the present invention has the following beneficial effects:

[0022] (1) Preparation of core-shell structured Cu@CuO and three-dimensional aerogel network-like Cu@Cu by redox method 2 O. The core-shell structure has a larger area and can contact more bacteria, improving the antibacterial properties of the material faster and better.

[0023] (2) The copper of the present invention has three mixed valence states, which improves the antibacterial property of copper. Among them, the 0-valent metallic copper quickly damages the cell membrane and destroys the integrity of the cell membrane; the 1-valent cuprous ion firmly binds to the sulfhydryl group of the protein molecule to inactivate the protein; the 2-valent copper can quickly damage the integrity of the cell membrane and specifically bind to DNA, resulting in cross-linking of the DNA chain and finally denaturation.

[0024] (3) The three-dimensional aerogel network has a larger porosity and stronger adsorption capacity, which can adsorb more bacteria on the surface of the material more quickly, causing the bacteria to be inactivated quickly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a three-dimensional aerogel network Cu@Cu in the embodiment of the present invention. 2 TEM image of O

[0026] Figure 2 This is a SEM cross-sectional view of the divalent copper ion antibacterial masterbatch of the embodiment of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1

[0029] 1) Preparation of Cu@CuO:

[0030] (1) An emulsion containing 20 mL of ethanol, 12 mL of deionized water, 6 mL of glycerol, and 3 g of soluble copper chloride was magnetically stirred for 1 h until uniformly mixed. The emulsion was then transferred to a high-pressure reactor and reacted at 200 °C for 8 h, followed by natural cooling to room temperature.

[0031] (2) The precipitate was removed from the reactor, washed with ethanol three times, and heated at 60 °C.

[0032] After drying in air for 3 h, Cu@CuO was obtained.

[0033] 2) Three-dimensional aerogel network Cu@Cu 2 Preparation of O:

[0034] (1) Add 4 g of soluble copper chloride and 1.6 g of strong base sodium hydroxide into deionized water and stir for 1 h until uniform. Then transfer the mixture into a three-necked flask and continue stirring for 20 min. Then, introduce inert gas argon for 20 min.

[0035] (2) Add 100 μL of ethanol to the above mixture, dissolve 12 g of reducing agent sodium borohydride in deionized water, and quickly add the reducing agent sodium borohydride solution to the above solution during stirring. After 15 minutes, centrifuge and wash with deionized water and anhydrous ethanol three times to obtain a three-dimensional aerogel network Cu@Cu 2 O.

[0036] 3) The Cu@CuO and three-dimensional aerogel network Cu@Cu prepared in step 1) and step 2) are 2O and polyethylene powder were mixed at a stirring speed of 550 rpm for 15 min to obtain a mixed powder, and then the mixed powder was heated to 130-210 °C by a twin-screw extruder granulator to melt and extrude, wherein the nine-stage processing temperature of the twin-screw extruder was set as follows: the temperature of the first zone was 130 °C, the temperature of the second zone was 165 °C, the temperature of the third zone was 188 °C, the temperature of the fourth zone was 198 °C, the temperature of the fifth zone was 210 °C, the temperature of the sixth zone was 210 °C, the temperature of the seventh zone was 200 °C, the temperature of the eighth zone was 180 °C, and the temperature of the ninth zone was 166 °C. After air cooling and pelletizing, a mixed-valence copper ion antibacterial masterbatch was obtained.

[0037] Embodiment 2

[0038] 1) Preparation of Cu@CuO:

[0039] (1) An emulsion containing 30 mL of ethanol, 20 mL of deionized water, 9 mL of glycerol, and 5 g of soluble copper sulfate was magnetically stirred for 2 h until uniformly mixed. The emulsion was then transferred to a high-pressure reactor and reacted at 240 °C for 6 h, and then naturally cooled to room temperature.

[0040] (2) The precipitate was removed from the reactor, washed with ethanol five times, and heated at 80 °C.

[0041] After drying in air for 2 h, Cu@CuO was obtained.

[0042] 2) Three-dimensional aerogel network Cu@Cu 2 Preparation of O:

[0043] (1) Add 6 g of soluble copper sulfate and 2.4 g of strong base potassium hydroxide into deionized water and stir for 2 h until uniform. Then transfer the mixture into a three-necked flask and continue stirring for 30 min. Then, introduce inert gas argon for 30 min.

[0044] (2) Add 150 μL of ethanol to the above mixed solution, dissolve 16 g of reducing agent hydrazine hydrate in deionized water, and quickly add the reducing agent hydrazine hydrate solution to the above solution during stirring. After 20 minutes, centrifuge and wash with deionized water and anhydrous ethanol for 5 times to obtain a three-dimensional aerogel network Cu@Cu 2 O.

[0045] 3) The Cu@CuO and three-dimensional aerogel network Cu@Cu prepared in step 1) and step 2) are 2O and polyethylene powder were mixed at a stirring speed of 600 rpm for 30 min to obtain a mixed powder, and then the mixed powder was heated to 130-210 °C by a twin-screw extruder granulator to melt and then extruded, wherein the nine-stage processing temperature of the twin-screw extruder was set as follows: the temperature of the first zone was 130 °C, the temperature of the second zone was 165 °C, the temperature of the third zone was 188 °C, the temperature of the fourth zone was 198 °C, the temperature of the fifth zone was 210 °C, the temperature of the sixth zone was 210 °C, the temperature of the seventh zone was 200 °C, the temperature of the eighth zone was 180 °C, and the temperature of the ninth zone was 166 °C. After air cooling and pelletizing, a mixed-valence copper ion antibacterial masterbatch was obtained.

[0046] Embodiment 3

[0047] 1) Preparation of Cu@CuO:

[0048] (1) An emulsion containing 30 mL of ethanol, 20 mL of deionized water, 9 mL of glycerol, and 5 g of soluble copper acetate was magnetically stirred for 2 h until uniformly mixed. The emulsion was then transferred to a high-pressure reactor and reacted at 240 °C for 6 h, and then naturally cooled to room temperature.

[0049] (2) The precipitate was removed from the reactor, washed with ethanol five times, and heated at 80 °C.

[0050] After drying in air for 2 h, Cu@CuO was obtained.

[0051] 2) Three-dimensional aerogel network Cu@Cu 2 Preparation of O:

[0052] (1) Add 6 g of soluble copper acetate and 2.4 g of strong base sodium hydroxide into deionized water and stir for 2 h until uniform. Then transfer the mixture into a three-necked flask and continue stirring for 30 min. Then, introduce inert gas nitrogen for 20 min.

[0053] (2) Add 150 μL of ethanol to the above mixture, dissolve 16 g of hypochlorous acid in deionized water, and quickly add the hypochlorous acid solution to the above solution during stirring. After 20 min, centrifuge and wash with deionized water and anhydrous ethanol for 5 times to obtain a three-dimensional aerogel network Cu@Cu 2 O.

[0054] 3) The Cu@CuO and three-dimensional aerogel network Cu@Cu prepared in step 1) and step 2) are 2O and polyethylene powder were mixed at a stirring speed of 700 rpm for 30 min to obtain a mixed powder, and then the mixed powder was heated to 130-210 °C by a twin-screw extruder granulator to melt and extrude, wherein the nine-stage processing temperature of the twin-screw extruder was set as follows: the temperature of the first zone was 130 °C, the temperature of the second zone was 165 °C, the temperature of the third zone was 188 °C, the temperature of the fourth zone was 198 °C, the temperature of the fifth zone was 210 °C, the temperature of the sixth zone was 210 °C, the temperature of the seventh zone was 200 °C, the temperature of the eighth zone was 180 °C, and the temperature of the ninth zone was 166 °C. After air cooling and pelletizing, a mixed-valence copper ion antibacterial masterbatch was obtained.

Claims

1. A method for preparing a mixed-valence copper ion antibacterial masterbatch, characterized in that: The specific steps of this method are: 1) Preparation of Cu@CuO: (1) An emulsion containing 20-30 mL of ethanol, 12-20 mL of deionized water, 6-9 mL of glycerol, and 3-5 g of soluble copper salt was magnetically stirred for 1-2 h until uniformly mixed, then transferred to a high-pressure reactor, reacted at 200-240 °C for 6-8 h, and naturally cooled to room temperature; (2) Take the precipitate out of the reactor, wash it with ethanol 3 to 5 times, and heat it at 60 to 80 °C. Dry in air for 2-3 h to obtain Cu@CuO; 2) Preparation of three-dimensional aerogel network Cu@Cu2O: (1) Add 4-6 g of soluble copper salt and 1.6-2.4 g of strong base into deionized water and stir for 1-2 h until uniform. Then transfer the mixture into a three-necked flask and continue stirring for 20-30 min. Then, introduce inert gas for 20-30 min. (2) Add 100-150 μL of ethanol to the above mixed solution, dissolve 12-16 g of reducing agent in deionized water, and quickly add the reducing agent solution to the above solution during stirring. After 15-20 min, centrifuge and wash with deionized water and anhydrous ethanol for 3-5 times to obtain a three-dimensional aerogel network Cu@Cu2O; 3) The Cu@CuO and three-dimensional aerogel network Cu@Cu2O prepared in step 1) and step 2) are mixed with polyethylene powder at a stirring speed of 550-750 rpm for 15-30 min to obtain a mixed powder, and then the mixed powder is heated to 130-210°C by a twin-screw extruder granulator, and then extruded after melting, air-cooled and pelletized to obtain a mixed valence copper ion antibacterial masterbatch. The soluble copper salt is one or a combination of copper chloride, copper sulfate or copper acetate. The strong base is sodium hydroxide or potassium hydroxide or a combination thereof, The inert gas is one or a combination of nitrogen or argon. The reducing agent is one or a combination of hydrazine hydrate, sodium borohydride or hypochlorous acid. The nine-stage processing temperature settings of the twin-screw extruder are: zone one temperature 130°C, zone two temperature 165°C, zone three temperature 188°C, zone four temperature 198°C, zone five temperature 210°C, zone six temperature 210°C, zone seven temperature 200°C, zone eight temperature 180°C, zone nine temperature 166°C.